2021
DOI: 10.1186/s13643-021-01762-x
|View full text |Cite
|
Sign up to set email alerts
|

Men’s sheds as community-based health promotion for men aged 50 plus: protocol for a mixed-methods systematic review

Abstract: Background Men are less likely to participate in health promotion. One approach to reach men is the concept of men’s sheds. This community-based health promotion concept brings older men together to engage in joint activities. Prior research revealed various health-related effects of men’s sheds, such as benefits for well-being and mental health. To strengthen the current evidence base of men’s sheds, a mixed-methods systematic review analysing the association between participation and self-rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…The aim of this paper was to describe the sociodemographic and health and wellbeing characteristics of a cohort of Shedders (n=384) who enrolled in a health promotion initiative (SFL) in the Shed setting. Previous studies have identified a distinct lack of such data [3,13,20,21], making it difficult to adjudicate on the merits of the Shed as a setting for targeted health promotion interventions or on what the composition of such initiatives should be. Findings will have an important bearing on the scale-up of SFL as well as highlighting areas where diversification is needed to respond effectively to the needs of the target group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this paper was to describe the sociodemographic and health and wellbeing characteristics of a cohort of Shedders (n=384) who enrolled in a health promotion initiative (SFL) in the Shed setting. Previous studies have identified a distinct lack of such data [3,13,20,21], making it difficult to adjudicate on the merits of the Shed as a setting for targeted health promotion interventions or on what the composition of such initiatives should be. Findings will have an important bearing on the scale-up of SFL as well as highlighting areas where diversification is needed to respond effectively to the needs of the target group.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside the utility of SFL in providing a template for structured health promotion in Sheds, there is also a need to address a deficit in the men's health literature in terms of the demographic of men who participate in health promotion in Sheds. Indeed, findings on Shed outcomes generally highlighted in previous scoping and narrative reviews, are predominantly based on small scale qualitative studies, with a distinct lack of information on the demographics of Shed participants, typically limited to age and gender [3,13,20,21]. Moreover, researchers have identified a lack of quantitative and mixed methods approaches, as well as limited use of validated measures to measure health outcomes [21].…”
Section: Men's Shed Members -Who Are They?mentioning
confidence: 99%
“…This mixed-methods systematic review is registered at the International Prospective Register of Systematic Reviews (PROSPERO; CRD42020219390) and a review protocol was published ( Albrecht et al, 2021 ). The recommendations of the “Manual for Evidence Synthesis” of the Joanna Briggs Institute (JBI) were followed ( Aromataris & Munn, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, findings on Shed outcomes generally highlighted in previous scoping and narrative reviews, are predominantly based on small-scale qualitative studies, with a distinct lack of information on the demographics of Shed participants, typically limited to age and gender. 3,13,22,23 Moreover, researchers have identified a lack of quantitative and mixed methods approaches, as well as limited use of validated measures to measure health outcomes, 23 which is a noted limitation in assessing the Shedhealth link. Understanding the characteristics of Shedders is important to tailor health promotion endeavours accordingly and to respond effectively to the needs of the target group.…”
Section: Men's Sheds Members-who Are They?mentioning
confidence: 99%
“…Alongside the utility of SFL in providing a template for structured health promotion in Sheds, there is also a need to address a deficit in the men's health literature in terms of the demographic of men who participate in health promotion in Sheds. Indeed, findings on Shed outcomes generally highlighted in previous scoping and narrative reviews, are predominantly based on small‐scale qualitative studies, with a distinct lack of information on the demographics of Shed participants, typically limited to age and gender 3,13,22,23 . Moreover, researchers have identified a lack of quantitative and mixed methods approaches, as well as limited use of validated measures to measure health outcomes, 23 which is a noted limitation in assessing the Shed‐health link.…”
Section: Introductionmentioning
confidence: 99%